Orientasi kewirausahaan dan kapabilitas pemasaran pada kinerja usaha kecil dan menengah: Peran faktor lingkungan yang dinamis sebagai pemoderasi - Dewi Lestari; Perengki Susanto (Jurnal Kajian Manajemen Bisnis, 2021)
The purpose of this study is to examine the impact of entrepreneurial orientation and marketing capabilities on the performance of small and medium-sized enterprises (SMEs), as well as how dynamic environmental factors moderate these relationships. The population was all managers or owners of SMES in Padang City. The sampling technique used a non-probability approach, namely the purposive sampling. In the data analysis, 190 samples (response rate 84,44%) were used as a sample size. The Smart-PLS software is used in this study to perform variance-based structural equation modeling (VB-SEM). The findings show that (i) entrepreneurial orientation has a positive and significant effect on SME performance, (ii) marketing capabilities have a positive and significant effect on SME performance, and (iii) In these relationships, the role of dynamic environmental factors as a moderator is not supported. The managerial implications will be discussed laterKeywords: Entrepreneurial orientation; marketing capabilities; dynamic environmental factors; performance; SMEs.